Чисельні дослідження кінетики десульфурації сталі при пневматичному перемішуванні - Тімошенко, С.М.; Смірнов, О.М.; Нємцев, Е.М. (Physico-technological Institute of Metals and Alloys, 2024)
Analysis of recent research and publications. In the conditions of mini-mills, the removal of sulfur in a number of cases is the limiting link in the production of steel. The kinetics of desulfurization is determined by the specific stirring power of the steel melting bath. The influence of the geometry of the bath on the efficiency of pneumatic mixing and desulfurization of steel at a fixed mass has not been sufficiently studied. Purpose and method. The purpose of the work is increasing the energy efficiency of steel production in the conditions of a mini-mill due to the minimization of steel desulfurization time. The method consists of numerical modeling of the desulfurization kinetics taking into account the geometric parameters of the steel melting bath and regime parameters of pneumatic mixing. Novelty and scientific significance of research. In the context of the kinetics of steel desulphurization, an understanding of the energy component of the process was developed through the specific power of pneumatic mixing of the liquid bath Nmix. The finiteness of the isothermal expansion model of the rising gas bubble for determining Nmix in industrial conditions through argon flow rate is shown. A mathematical model for estimating Nmix when purging the bath with argon in jet-bubble mode through the averaged speed of liquid steel movement and Archimedes’ force as a function of the gas content ratio in the two-phase region is proposed. The model allows optimizing argon flow rate according to the criterion of the maximum specific power of pneumatic mixing. This mode ensures the minimum duration of steel desulfurization for the given slag parameters and geometry of the steel melting bath-bottom porous plug system. Practical value. Determining the optimal flow rate of argon to ensure the maximum specific power of pneumatic mixing of a steel melting bath of a certain geometry and mass in the context of minimizing the duration of desulfurization contributes to increasing the energy efficiency of the steel production technology in the conditions of mini-mill operation.